Garlic As Antibacterial in Lactose Fermenter Enterobacteriaceae - Reina Puspita Rahmaniar; Dyah Widhowati; Nurul Hidayah (JURNAL KAJIAN VETERINER, 2023)
This study attempts to investigate the antibacterial effectiveness of three varieties of garlic (single garlic, kating garlic, and black garlic) on the growth of Enterobacteriaceae bacteria (Escherichia coli, Enterobacter sp, Klebsiella sp. from chicken meat samples. Treatment Kating garlic, single garlic, and black garlic at concentrations of 20%, 40%, 60%, 80%, 90%, 100%. This study observed the inhibition zone on Muller Hinton Agar (MHA) media that had been planted with bacterial isolates. The inhibition test uses the disk diffusion method. The findings revealed that kating garlic and single garlic showed inhibition zones against Escherichia coli, Enterobacter sp., and Klebsiella sp. bacteria. Meanwhile, black garlic did not show an inhibition zone against E. coli bacteria, but showed an inhibition zone against Klebsiella sp., Enterobacter sp., and Kating garlic had the largest bacterial inhibition zone against E. coli, Klebsiella sp., Enterobacter sp., followed by single garlic.